Factors influencing in selection of Online banking products: a conceptual paper on Bangladeshi customer - Uddin, Bashir; Haque, A. K. M. Ahasanul; Swain, Dindayal (2017)
The study has been led to research the components that impact the clients of electronic banking services to utilize internet banking in Bangladesh. In this study there has been utilizing diverse compelling components that has an extraordinary effect to rouse or impact the internet banking client in determination of their web based banking framework in Bangladesh will be examine and with different analytical procedures. It has been seen from the result of the literature that, the ease of usefulness is the most critical component that impacts the client in choice of internet Abstract: banking. Different questions will be asked to determine the most influencing term under use of usefulness. On perception, a proper policy may go a long way to increase the ease use online banking system with the improvement of other related facilities which will help the online banking system to attract the new clients.